Diabetic Mouse Delayed Wound Model Following Treatment with the NerveStim™ Neuropathy System - Kalmeta Margaret; Sanders Mitchell; Siegmund Nikole; Hanna Mia; M. Salam Akram; Pasciak Christine (Journal of Tissue Repair and Regeneration, 2026)
Delayed wound healing in diabetes is characterized by impaired angiogenesis, persistent inflammation, extracellular matrix dysregulation, and peripheral neuropathy. A preclinical study was conducted using a diabetic mouse delayed wound model to evaluate the surrounding tissue of a wound, (its periwound) and its tissue responses following treatment with the NerveStim™ Neuropathy System, a combination topical gel and neuromuscular electrical stimulation platform. Periwound tissue was harvested at Day 14 and analyzed using NanoString gene expression profiling. Treated animals demonstrated visibly increased periwound tissue thickness compared to untreated controls. Differential expression analysis identified 76 significantly upregulated and 17 downregulated genes. Upregulated pathways included angiogenesis (Vegfa, Fgf2, Pdgfb, Nos3), neurotrophic signaling (Ngf, Bdnf, Scn9a, Trpv1), macrophage polarization (Arg1, Mrc1, Il10), and extracellular matrix remodeling (Col1a1, Col3a1, Mmp9, Timp1). Downregulation of select pro-inflammatory mediators (Nos2, Mif) was observed. These coordinated transcriptional changes are consistent with activation of reparative immune, neurovascular, and matrix remodeling pathways in diabetic periwound tissue.
Keywords: diabetic wound model